Weight change in the early rheumatoid arthritis period and risk for subsequent mortality among women with RA and matched comparators - Sparks, Jeffrey A. (Arthritis Rheumatol, 2017)
OBJECTIVE: We investigated whether weight change during the early RA period was associated with subsequent mortality and evaluated for an RA-specific effect. METHODS: We identified incident RA during the Nurses’ Health Study (1976–2016) and created a comparison cohort, matching each RA case with up to 10 non-RA comparators by age and year of RA diagnosis (index date). To capture weight change around the early RA period (“peri-RA/index”), we used weight measures 2–4 years before and after index date. Cox regression estimated HRs for mortality by peri-RA/index weight change categories separately in each cohort and combined, evaluating for an RA-specific effect. RESULTS: Among 121,701 women, 902 developed incident RA, matched to 7,884 non-RA comparators. There were 371(41.1%) deaths in the RA cohort during mean 17.0 years follow-up after the early RA period and 2,303(29.2%) deaths among comparators during mean 18.4 years follow-up. Peri-RA weight loss >30 lb had HR of 2.78 (95%CI1.58–4.89) for mortality compared to stable weight; the comparison cohort had similar results (HR 2.16, 95%CI1.61–2.88). Weight gain >30 lb had no association with mortality among RA (HR 1.45, 95%CI0.69–3.07) or comparators (HR 1.19, 95%CI0.89–1.59). There was no interaction between RA/comparator status and weight change for mortality (p(interaction)=0.68). CONCLUSION: Severe weight loss during the early RA period was associated with increased subsequent mortality risk for women with and without RA. These results extend prior observations by including non-RA comparators and finding no protective association between weight gain and mortality, arguing against an RA-specific obesity paradox for mortality.